The Relationship between Strategic Targets and Measurement: Structuring a Calibration Model of Planning, Measuring, and Implementing Performance Considering Non-financial Factors - Adrienn Lajo (European Scientific Journal, ESJ, 2023)
Institutions and sub-organizations that manage public funds show differences in many aspects, whether taking into account their tasks, financing, or structure. The difference is even greater when looking at an overview of organizations operating in the competitive sector. However, performance, its measurement and the management of changes based on these are the main characteristics of quality-oriented management. The issue is furtherly complicated by the topic of sustainability and its measurement ability and capacity. For the sake of sustainability, not only business processes but also administrative organizations must strive for excellence today. This is supported by the fact that the functioning of a value-oriented organization, and the development of its processes in accordance with it, can be characterized by a strategic perspective (that is, long-term targeted goals) and a “customer-oriented” approach. It would be too simplistic to assume that by measuring everything adequately and accurately, we can approach the authentic analysis and evaluation of performance, as in the case of a multinational giant, for example, this comprehensive and detailed coverage unnecessarily complicates the measurement system and inevitably leads to obstacles and errors. Based on professional approaches, good performance and the path to achieving it, as well as maintaining the results achieved, can be broken down into parts and, as such, we can strive to improve the whole by optimizing the parts. However, it is also a fact that the improvement of individual parts often contradicts each other, that processes can become dependent or even divergent, so perhaps we can achieve the most if we follow these from multiple dimensions, according to multiple points and principles, and consider the quality of the whole, as a unit, as a superior principle of part optimization. One significant element of this is that management defines and manages conscious action, that is, measures, then defines the expected in relation to reality: plans; directs the change process; measures the results; analyzes the effects; and at the same time places information in a decision-making hierarchy for the functioning and task fulfillment of the organization. This is also characterized by the maintenance of performance and the guarantee of sustainability.In the processes of public service institutions, if we want to identify the criteria for expected performance, starting from the social usefulness and the concept of good governance - that is, why it is important to provide tasks in the most convenient and qualitative way - we will get to the importance of good organization management, efficient and efficient operation, quality management, creation of added value, and professional activity. Through the measurement of processes and the management of changes and the sustainability of goals. (In the public sector, performance is interpreted in the 3E or 4E framework, that is, economy, efficiency, effectiveness, and equity give a deep segmentation of performance.  ) In the competitive sector, apart from the profit-oriented goal system, performance is determined by the expectations of the market, social, ecological, or political-legal environment, its adaptation, and not only its momentary state but its sustainability. Performance can only be expressed in one or a few specific indicators or parameters in the rarest cases. Even in the most streamlined profile organizations, we are talking about a more complex problem. This study, starting from this thought, shows how performance management, a management tool (usually organizational measurement), its trained and applied model (GAP: Gain Advanced Performance) can be connected in practice, how a set of points represented in a competitive sector and a theoretical model of an administrative organization can be made accessible with what approach, and how this can contribute to the efficiency of organizations in terms of state and shareholder expectations.